LAYANAN BIMBINGAN KELOMPOK TENTANG PERILAKU AGRESIF PADA PESERTA DIDIK KELAS XI SEKOLAH MENENGAH ATAS NEGERI 9 PONTIANAK - Kesi, Kesi; Asrori, M; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study contained group guidance services behavior to year-11 studens of senior High School 9 Pontianak. The problem this study aimed to obtain an overview and describe the types of aggressive behavior, the formation stage, the transition stage, the activity stage, and the termination stage. The method of this research was descriptive method with the form of research used, namely survey. The research subjcts were year-11 students in total 25 students. The techniques and tools used in this study were indirect communication with questionnaires. Based on the result of data analysis, a group guidance services on aggressive behavior can be seen in the acquisition of percentage results for each including: 1. Types of aggressive behavior 75%, 2. Stage of formation 81,26%, 3. Transition stage 80% 4. Stage activities 86.50%, 5. Termination stage 83,56%. Based on the description above, in general, a group guidance services had been successfully carried out on year-11 students of Senior High School 9 Pontianak. Therefore, this group guidance services were suitable to be applied in other classes to overcome the aggressive behavior. Keywords: Aggressive Behavior, Group Guidance Services